KCNT1-related epilepsies and epileptic encephalopathies: phenotypic and mutational spectrum - Bonardi, Claudia M.; Heyne, Henrike O; Fiannacca, Martina; Fitzgerald, Mark P; Gardella, Elena; Gunning, Boudewijn; Olofsson, Kern; Lesca, Gaétan; Verbeek, Nienke; Stamberger, Hannah; Striano, Pasquale; Zara, Federico; et al. (Brain, 2021)
Variants in KCNT1, encoding a sodium-gated potassium channel (subfamily T member 1), have been associated with a spectrum of epilepsies and neurodevelopmental disorders. These range from familial autosomal dominant or sporadic sleep-related hypermotor epilepsy to epilepsy of infancy with migrating focal seizures (EIMFS) and include developmental and epileptic encephalopathies. This study aims to provide a comprehensive overview of the phenotypic and genotypic spectrum of KCNT1 mutation-related epileptic disorders in 248 individuals, including 66 previously unpublished and 182 published cases, the largest cohort reported so far.Four phenotypic groups emerged from our analysis: (i) EIMFS (152 individuals, 33 previously unpublished); (ii) developmental and epileptic encephalopathies other than EIMFS (non-EIMFS developmental and epileptic encephalopathies) (37 individuals, 17 unpublished); (iii) autosomal dominant or sporadic sleep-related hypermotor epilepsy (53 patients, 14 unpublished); and (iv) other phenotypes (six individuals, two unpublished). In our cohort of 66 new cases, the most common phenotypic features were: (i) in EIMFS, heterogeneity of seizure types, including epileptic spasms, epilepsy improvement over time, no epilepsy-related deaths; (ii) in non-EIMFS developmental and epileptic encephalopathies, possible onset with West syndrome, occurrence of atypical absences, possible evolution to developmental and epileptic encephalopathies with sleep-related hypermotor epilepsy features; one case of sudden unexplained death in epilepsy; (iii) in autosomal dominant or sporadic sleep-related hypermotor epilepsy, we observed a high prevalence of drug-resistance, although seizure frequency improved with age in some individuals, appearance of cognitive regression after seizure onset in all patients, no reported severe psychiatric disorders, although behavioural/psychiatric comorbidities were reported in ∼50% of the patients, sudden unexplained death in epilepsy in one individual; and (iv) other phenotypes in individuals with mutation of KCNT1 included temporal lobe epilepsy, and epilepsy with tonic-clonic seizures and cognitive regression.Genotypic analysis of the whole cohort of 248 individuals showed only missense mutations and one inframe deletion in KCNT1. Although the KCNT1 mutations in affected individuals were seen to be distributed among the different domains of the KCNT1 protein, genotype-phenotype considerations showed many of the autosomal dominant or sporadic sleep-related hypermotor epilepsy-associated mutations to be clustered around the RCK2 domain in the C terminus, distal to the NADP domain. Mutations associated with EIMFS/non-EIMFS developmental and epileptic encephalopathies did not show a particular pattern of distribution in the KCNT1 protein. Recurrent KCNT1 mutations were seen to be associated with both severe and less severe phenotypes.Our study further defines and broadens the phenotypic and genotypic spectrums of KCNT1-related epileptic conditions and emphasizes the increasingly important role of this gene in the pathogenesis of early onset developmental and epileptic encephalopathies as well as of focal epilepsies, namely autosomal dominant or sporadic sleep-related hypermotor epilepsy.
Gesehen am 07.02.2023